An Iron-Catalyzed Direct Approach to Amides from Benzyl Azides via C–C Bond Cleavage - Ou, Yang; Qin, Chong; Song, Song; Jiao, Ning (Synthesis, 2015)
A novel iron-catalyzed transformation of benzyl azides to give the corresponding amides via C–C bond cleavage under mild reaction conditions is developed. This method provides a new synthetic tool for the construction of amides and the opportunity to accomplish C–C functionalization under mild conditions.
Keywords: C–C bond cleavage; azides; amides; rearrangement